Nanochemistry a chemical approach to nanomaterials - Ozin, Geoffrey A. (Royal Society of Chemistry, 2009)
This textbook on nanochemistry adopts an interdisciplinary and comprehensive approach to the subject. It presents a basic chemical strategy for making nanomaterials and describes some of the principles of materials self-assembly over 'all' scales.